Arsenic tolerance and biosorption by Rhizobacteria isolated from Rhizosphere zone of Pennisetum purpureum grown in arsenic contaminated sand - Rahman, Md Ekhlasur; Mahmud, Khairil; Uddin, Md Kamal; Shamsuzzaman, S. M.; Abd Shukor, Mohd Yunus; Abd Ghani, Siti Salwa; Akter, Amaily; Nabayi, Abba; Sadeq, Buraq Musa; Chompa, Sayma Serine; Halmi, Mohd Izuan Effendi (Taylor and Francis, 2025)
Several rhizobacteria can be utilized in bioremediation or phytoremediation to eliminate arsenic from the ecosystem. The goal of this research is to measure the minimum inhibitory concentration (MIC), arsenic tolerance, and biosorption capability of rhizobacteria that were separated from the rhizosphere zone of Pennisetum purpureum plants. All the identified rhizobacteria showed greater number of MIC value and were able to uptake significant amount of arsenic. Among them 28N U UPM (Bacillus australimaris) displayed the maximum MIC value and arsenic biosorption capability of 9000 mg L−1 arsenic and 45.02 ± 0.14 mg g−1dry cell weight (DCW) separately. Besides, all the identified rhizobacteria showed excellent results in terms of arsenic tolerance such as bacterial growth, exopolysaccharide production, biofilm formation, and floc yield production. Kinetic model study demonstrated that 28N U UPM (Bacillus australimaris) (R2 = 0.99, 0.92, and 0.94) and 28N H UPM (Burkholderia seminalis) (R2 = 0.99, 0.92, and 0.94) followed the pseudo-first-order, pore diffusion, and Elovich kinetic models. The selected rhizobacteria vary in their mechanism of arsenic tolerance, arsenic biosorption ability, and kinetic models in arsenic biosorption. So, these nine identified rhizobacteria can be used as effective tool for bioremediation or phytoremediation of arsenic in polluted environment.